The answer is d. -14 + (-6)
Answer:
√(p²-4q)
Step-by-step explanation:
Using the Quadratic Formula, we can say that
x = ( -p ± √(p²-4(1)(q))) / 2(1) with the 1 representing the coefficient of x². Simplifying, we get
x = ( -p ± √(p²-4q)) / 2
The roots of the function are therefore at
x = ( -p + √(p²-4q)) / 2 and x = ( -p - √(p²-4q)) / 2. The difference of the roots is thus
( -p + √(p²-4q)) / 2 - ( ( -p - √(p²-4q)) / 2)
= 0 + 2 √(p²-4q)/2
= √(p²-4q)
Answer:
x=3
Step-by-step explanation:
0=(x+2)^2-25
+25 +25
25=(x+2)^2
Square root both sides to get:
5=x+2
-2 -2
3=x
Answer:
P(Z < 2.37) = 0.9911.
Step-by-step explanation:
We are given that Let z denote a random variable that has a standard normal distribution.
Let Z = a random variable
So, Z ~ Standard Normal(0, 1)
As we know that the standard normal distribution has a mean of 0 and variance equal to 1.
Z =
~ N(0,1)
where,
= mean = 0
= standard deviation = 1
Now, the probability that z has a value less than 2.37 is given by = P(Z < 2.37)
P(Z < 2.37) = P(Z <
) = P(Z < 2.37) = 0.9911
The above probability is calculated by looking at the value of x = 2.37 in the z table which has an area of 0.9911.